A novel synthetic smoothened antagonist transiently inhibits pancreatic adenocarcinoma xenografts in a mouse model. - Martin F Strand; Steven R Wilson; Jennifer L Dembinski; Daniel D Holsworth; Alexander Khvat; Ilya Okun; Dirk Petersen; Stefan Krauss (PLoS ONE, 2011)
Hedgehog (Hh) signaling is over-activated in several solid tumors where it plays a central role in cell growth, stroma recruitment and tumor progression. In the Hh signaling pathway, the Smoothened (SMO) receptor comprises a primary drug target with experimental small molecule SMO antagonists currently being evaluated in clinical trials.Using Shh-Light II (Shh-L2) and alkaline phosphatase (AP) based screening formats on a "focused diversity" library we identified a novel small molecule inhibitor of the Hh pathway, MS-0022 (2-bromo-N-(4-(8-methylimidazo[1,2-a]pyridin-2-yl)phenyl)benzamide). MS-0022 showed effective Hh signaling pathway inhibition at the level of SMO in the low nM range, and Hh pathway inhibition downstream of Suppressor of fused (SUFU) in the low µM range. MS-0022 reduced growth in the tumor cell lines PANC-1, SUIT-2, PC-3 and FEMX in vitro. MS-0022 treatment led to a transient delay of tumor growth that correlated with a reduction of stromal Gli1 levels in SUIT-2 xenografts in vivo.We document the in vitro and in vivo efficacy and bioavailability of a novel small molecule SMO antagonist, MS-0022. Although MS-0022 primarily interferes with Hh signaling at the level of SMO, it also has a downstream inhibitory effect and leads to a stronger reduction of growth in several tumor cell lines when compared to related SMO antagonists.